Constructing mathematical bitterness scale related to teacher factor - Dirgantoro, Kurnia Putri Sepdikasari; Soesanto, Robert Harry; Yanti, Yanti (Jurnal Elemen, 2024)
Mathematical bitterness is one of the critical factors influencing students’ mathematical performance, highlighting the need for further action to address its impact.  However, there has been no instrument thus far that can identify mathematical bitterness, particularly one caused by teacher treatment. This research, therefore, aims to construct an instrument to identify the presence of mathematical bitterness. This research involved 307 senior high school and undergraduate students, who were given and responded to a set of 30 questions. The data were then analyzed using confirmatory factor analysis (CFA) through IBM SPSS 20. Confirmatory factor analysis grouped the items into six dimensions (indicators) of mathematical bitterness. Each indicator shows a high Cronbach Alpha result, indicating strong validity in each group of indicators. Overall, the constructed instrument demonstrates strong validity and reliability. This instrument has been successfully constructed and statistically tested, thus making it readily available for use by other scholars interested in investigating mathematical bitterness on a broader scale.